PENGARUH KOLABORASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN KONSENTRASI KEAHLIAN ELEMEN KOMUNIKASI DI TEMPAT KERJA KELAS XI MP SMK NEGERI 1 MEDAN - Barus, Sindari; Tauada Silalahi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the collaborative implementation of the Problem Based Learning (PBL) and Role Playing learning models on students' learning outcomes in the Workplace Communication Element of the Office Management and Business Services program for Grade XI students at SMK Negeri 1 Medan in the 2025/2026 academic year. This study employed a quasi-experimental method using a Nonequivalent Control Group Design and a total sampling technique. Data were analyzed using the Shapiro-Wilk normality test, homogeneity test, Independent Sample t-test, and N-Gain test. The research instruments were tested for validity, reliability, discrimination index, and difficulty level.The results showed that the experimental group's mean pre-test score increased from 46.67 to 79.56 in the post-test, while the control group's mean score increased from 49.52 to 67.43. The normality test indicated that the data were normally distributed, and the homogeneity test showed that the data were homogeneous with a significance value of 0.092 > 0.05. The hypothesis test yielded a significance value of 0.000 < 0.05, indicating a significant effect on students' learning outcomes. Furthermore, the N-Gain analysis revealed that the experimental group achieved an average score of 59.95%, categorized as moderately effective, while the control group obtained an average score of 34.21%, categorized as ineffective. Based on the findings, it can be concluded that the collaborative implementation of the Problem Based Learning (PBL) and Role Playing learning models has a significant and moderately effective impact on improving students' learning outcomes in the Workplace Communication Element for Grade XI students at SMK Negeri 1 Medan.